Kualitas Spermatozoa Sapi Peranakan Limousin dalam Pengencer AndroMed yang Ditambahkan Berbagai Level Glukosa - Eril Rista Putra; Khaeruddin Khaeruddin; Andi K urnia Armayanti; Sitti Farida; Syamsiar Amin (Faculty of Agriculture, Musamus University, 2022)
A good semen diluent should have a high preservation ability, the addition of simple sugar such as glucose can act as a source of energy and a cryoprotectant for spermatozoa. The purpose of this study was to determine the effect of adding glucose in the AndroMed® diluent to the sperm quality of Limousin crossbreed bull during the cryopreservation process. This study used a completely randomized design (CRD) with 5 treatment levels and 5 replications. The level of treatment used was diluted semen with added 0, 0.4, 0.6, 0.8 and 1% glucose, respectively. Semen was collected using an artificial vagina, diluted, and packaged in straws with a minimum concentration of 25 million spermatozoa per straw. Straw was equilibrated for 2 hours at 5 oC. The next step is prefreezing, freezing, and thawing at 37 oC for 30 seconds. Parameters observed were sperm viability and abnormality after equilibration and recovery rate. The results showed that the addition of glucose in the AndroMed® diluent had a very significant effect (P<0.01) on the sperm viability after equilibration, but had no effect (P>0.05) on the sperm abnormality after equilibration and the recovery rate of spermatozoa after freezing. The addition of 0.6 to 0.8% glucose was able to increase the sperm viability (91.2-94.49%). The conclusion of this study was that the addition of glucose in the AndroMed® diluent only affected the sperm viability of Limousin crossbreed bull after equilibration and the best glucose percentages used were 0.6%.